2021
DOI: 10.3390/diagnostics11112098
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of BIOCHIP Mosaic-Based Indirect Immunofluorescence with Enzyme-Linked Immunosorbent Assay for Diagnosing Myasthenia Gravis

Abstract: Background: The detection of anti-acetylcholine receptor (AChR) and anti-muscle-specific tyrosine kinase (MuSK) antibodies is useful in myasthenia gravis (MG) diagnosis and management. BIOCHIP mosaic-based indirect immunofluorescence is a novel analytical method, which employs the simultaneous detection of anti-AChR and anti-MuSK antibodies in a single miniature incubation field. In this study, we compare, for the first time, the BIOCHIP MG mosaic with conventional enzyme-linked immunosorbent assay (ELISA) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…A previous study showed that the overall concordance between BIOCHIP mosaic-based indirect immunofluorescence and ELISA for anti-MuSK reactivity was 84%. 34 However, in our study, the same serum sample was not tested by both methods at the same time, and the number of samples was small, so we could not compare the sensitivities of the two methods. Therefore, more studies with larger numbers of samples are needed to compare the role of different detection methods for detecting antibodies in the diagnosis of MG.…”
Section: Discussionmentioning
confidence: 93%
“…A previous study showed that the overall concordance between BIOCHIP mosaic-based indirect immunofluorescence and ELISA for anti-MuSK reactivity was 84%. 34 However, in our study, the same serum sample was not tested by both methods at the same time, and the number of samples was small, so we could not compare the sensitivities of the two methods. Therefore, more studies with larger numbers of samples are needed to compare the role of different detection methods for detecting antibodies in the diagnosis of MG.…”
Section: Discussionmentioning
confidence: 93%
“…To date, only a few studies have evaluated the performance of F-CBAs for anti-AChR detection. We previously demonstrated that the F-CBA for MG diagnosis did not accurately identify low anti-AChR and anti-MuSK levels, which were detected by an ELISA [26]. Mirian et al showed that F-CBAs have similar specificity and higher sensitivity compared to RIPAs but lower performance than L-CBAs [22].…”
Section: Discussionmentioning
confidence: 98%
“…Testing for autoantibodies (i.e., anti-AChR, anti-GAD) was performed by the radioimmunoassay method using a radio-receptor assay kit. The results were reported as positive for AChR if > 0.50 nmol/l, and positive for anti-GAD if > 5.0 UI/ml [16]. All the MG patients underwent total IgG, thyroid hormones and thyroid stimulating hormone serum testing, antinucleus antibodies testing, complete blood count, creatinine, blood urea nitrogen, liver transaminases, gamma glutamyl transferase, and total and fractionated bilirubin.…”
Section: Methodsmentioning
confidence: 99%